IMPROVING THE LAE-LAE ISLAND ENVIRONMENT AND SETTLEMENT QUALITY AS A MARINE TOURISM DESTINATION IN MAKASSAR CITY - Idawarni Asmal (Journal of Architecture&ENVIRONMENT, 2016)
Lae-Lae is an island in the city of Makassar, Indonesia. The island area of 0.04 sqkm, inhabited by 420 families or about 1780 inhabitants, is located 1.5 km from Makassar and accessible in 10 minutes with a fishing boat from the city of Kayu Bangkoa port. Lae-Lae island has excellent potential for tourist development of Makassar city, and a paradise for fans of sunset. In addition, there are also historical sites of war comprising an underground tunnel, which was said to connect to the fortress city of Makassar / Fort Rotterdam. Conditions of Lae-Lae island today feel less than comfortable because of the condition of the heat and lack of shade to enjoy the sunset. In addition, the attractions offered are also still very poor compared with its potential. Another thing deemed less supportive of Lae-Lae as a tourist destination in the past was the condition of facilities. To improve the quality of Lae-Lae island as a tourist destination, it would be necessary to arrange development of new tourist objects and improvement in the attractions that already exist. So the potential of the island as a travel destination can be optimized. The goal was to plan the arrangement of Lae-Lae island, both the environmental aspects and the settlement, so that Lae-Lae can be an optimal attraction for fans of nautical tourism, both locally and internationally. The method used was direct observation in the field through recordings, interviews, and of the conditions that exist today, which would then be linked to theories, concepts, and literature, also field trip to other tourist attractions that are more advanced. Results were in the form of settlement planning and Lae-Lae island environmental improvement that would be safe, comfortable and of tourism value.